(untitled) (Bangladesh Pharmaceutical Journal, 2019)
The present investigation was focused on formulation and in-vitro evaluation of a fixed dose bilayer tablet of two prominent antihypertensive agents, atenolol and amlodipine. The tablets were designed to immediately release atenolol (ATF1-ATF5) by using different percentage of sodium starch glycolate as super-disintegrant for prompt blood pressure lowering activity and sustain release amlodipine (AMF1- AMF5) by varying the percentage of hydroxy propyl methylcellulose (HPMC) for prolonged activity. After evaluation of the physical and chemical parameters of the formulations according to United States Pharmacopoeia (USP) guidelines, the best immediate release formulation was found in ATF1 in terms of dissolution (99.87% after 45 minutes) and other tablet properties like hardness, disintegration time, good flow properties etc. However, the best sustained release activity was found in AMF3 in terms of dissolution (99.98% after 24 hours with constant release) and other tablet properties. After optimization of the formulations, both atenolol and amlodipine parts were successfully compressed into bilayer tablets and post-compression parameters were evaluated. In 0.1 N HCl medium, the release of atenolol from bilayer tablet was found 98.97% after 45 minutes and in case of amlodipine it was found 98.12% in 0.1 N HCl medium followed by phosphate buffer medium after 24 hours. Drug release kinetics showed that the atenolol layer followed Case I, QasiFickian transport and amlodipine layer followed Anomalous (non-Fickian) transport. Compatibility study was conducted by using Fourier Transform Infrared Spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC). Moreover, crystalline nature of substances and extent of its conversion to amorphous form was studied using X-ray Diffractometry (X-RD). Bangladesh Pharmaceutical Journal 22(2): 153-169, 2019